Does Public–Private Partnership Investment in Energy Facilitate Electricity Generation from Renewable Energy Sources? - Farah Durani; Soo Khoon Goh; Ahsan Anwar; Qasim Raza Syed (Annals of Financial Economics, 2026)
The environmental challenges in China emanate from different sources, particularly fossil fuel consumption. The wave of industrialization has increased energy demand and compromised the environment’s quality. Over the years, policymakers in China have devised several methods, including public–private partnership (PPP) investments, to phase out fossil fuel consumption and encourage renewable energy generation. Based on this discourse, this study explores the effect of PPP investment in energy (PPPIE) on electricity generation from renewable sources (EPR). For the current analysis, a time series dataset for China is adopted that covers the period 1989–2022. Moreover, the novel augmented ARDL (AARDL) approach is employed. The results from the novel AARDL approach suggest that PPPIE increases EPR in both time horizons (i.e., the long- and short-run). Further, the findings from the novel wavelet quantile regression (WQR) delineate that PPPIE escalates EPR across the quantiles during all selected time horizons. Also, a one-way causality flows from PPPIE and economic growth to EPR. Besides, a bidirectional causality exists between inflation and EPR. No direction of causality exists between growth and inflation or between growth and PPPIE. Our findings recommend promoting PPPIE in China to achieve SDG7.